2022
DOI: 10.1080/22221751.2022.2059401
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of inactivated SARS-CoV-2 vaccines in people living with HIV

Abstract: It is important to know the safety and efficacy of vaccination in immunocompromised people living with HIV (PLWH), but currently, there is limited data on the inactivated SARS-CoV-2 vaccines’ safety and immune responses in PLWH. In this prospective observational study, 139 PLWH and 120 healthy controls were enrolled and monitored for 21–105 days after a two-dose vaccination. The safety, anti-receptor binding domain IgG (anti-RBD-IgG) and anti-spike-IgG responses, and RBD-specific memory B cell (MBC) responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 35 publications
13
69
0
Order By: Relevance
“…Our results were consistent with previous studies showing that PLWH had a lower immune response to inactivated COVID-19 vaccines than HNC ( 11 , 17 ). Studies by cross-sectional analysis showed that the level of nAbs in PLWH was lower than the levels in HNC at different time points after the second dose of the inactivated COVID-19 vaccination ( 17 , 18 ). However, no studies have compared peak humoral immune response in PLWH and HNC groups.…”
Section: Discussionmentioning
confidence: 98%
“…Our results were consistent with previous studies showing that PLWH had a lower immune response to inactivated COVID-19 vaccines than HNC ( 11 , 17 ). Studies by cross-sectional analysis showed that the level of nAbs in PLWH was lower than the levels in HNC at different time points after the second dose of the inactivated COVID-19 vaccination ( 17 , 18 ). However, no studies have compared peak humoral immune response in PLWH and HNC groups.…”
Section: Discussionmentioning
confidence: 98%
“…Memory B cells (MBCs) are considered to play an essential role in durable humoral immunity (Ao et al, 2022), and we next evaluated the frequency of RBD-specific MBCs in each group. The gating strategy and representative results are shown in Supplementary Figure 3.…”
Section: Memory B-cell Responses To Sars-cov-2 Inactivated Vaccinesmentioning
confidence: 99%
“…When the first dose of vaccine was given, RBD-specific memory B cells were generated and differentiated into antibody-secreting plasma cells when the second dose of vaccine was administered (Oliviero et al, 2020a). Our previous study found that the frequency of RBD-specific MBCs in immunocompromised people was decreased, which may lead to a lower seroprevalence of anti-RBD-IgG (Ao et al, 2022). For cancer patients, however, the frequency of MBCs and its correlation with antibody titer have not been fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…[ 66 ] Several studies have shown that immunogenicity after inactivated booster vaccination (BBIBP-CorV or CoronaVac) is negatively affected by low CD4 + T cell counts. [ 67 , 68 ] Recently, a new study evaluated the immune response to the CoronaVac vaccine in immunocompromised patients, and the proportion of PLWH who achieved neutralizing antibody positivity and total anti-SARS-CoV-2 IgG antibodies was significantly lower than that in the control group. PLWH with CD4 + T cell counts >500 cells/μL had higher seroconversion rates, neutralizing antibody positivity, and functional activity.…”
Section: Overview Of Sars-cov-2 Vaccination In Plwhmentioning
confidence: 99%
“…[ 71 ] For vaccination with inactivated virus, the overall incidence of adverse events within 7 days was similar between PLWH and healthy controls. [ 67 ] Currently, inactivated vaccines do not induce serious adverse events in PLWH. Indeed, the proportion of adverse reactions in PLWH inoculated with inactivated vaccines was significantly lower than that in PLWH that received mRNA vaccines.…”
Section: Overview Of Sars-cov-2 Vaccination In Plwhmentioning
confidence: 99%